Emergence of PER-2 and VEB-1a in Acinetobacter baumannii strains in the Americas - Pasteran, Fernando (2006)
Fil: Pasteran, Fernando. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio de Antimicrobianos; Argentina.